ANALYSIS OF THE WATER QUALITY OF POST-MINING LAKE BUKIT SEMPAJA INDAH BASED ON BOD, COD, AND DO PARAMETERS - Nabila Putri Shakila; Gadis Nindi Aprilia; Masitah Masitah; Dimas Adhitya Wardiman Setyawan (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2026)
Lake Bukit Sempaja Indah is a post-mining water body utilized by the surrounding community for various activities, making water quality monitoring necessary to assess its condition against applicable quality standards. This study aimed to evaluate the water quality of Lake Bukit Sempaja Indah based on Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and Dissolved Oxygen (DO). A descriptive quantitative approach was employed using purposive sampling at one sampling point representing an area with intensive community activities. Water samples were collected in January 2026 and analyzed in the laboratory according to Indonesian National Standards (SNI). The results showed that BOD, COD, and DO values were 1.84 mg/L, 11.10 mg/L, and 4.44 mg/L, respectively. All parameters met the Class II water quality standards stipulated in Government Regulation of the Republic of Indonesia No. 22 of 2021. The BOD and COD values indicated a relatively low organic pollution load, while the DO concentration indicated sufficient dissolved oxygen to support aquatic organisms. Based on measurements at the sampling point and during the sampling period, the water quality of Lake Bukit Sempaja Indah met Class II water quality standards based on BOD, COD, and DO parameters. Further monitoring at multiple locations and sampling periods, along with additional water quality parameters, is recommended to provide a more comprehensive assessment of the lake's condition.